THE UNSEEN ENEMY: A SCIENTIFIC EXPLORATION OF DIGITAL RISKS, IMPLICATIONS OF DIGITAL RISKS, THREATS, AND SCAMS ON USERS’ WELLBEING - Umurzoqov Mexroj Umar o`g`li (TADQIQOTLAR.UZ, 2023)
Abstract: The main objectives of the article, the concept of digital risks, their types, the causes they cause, methods of Prevention, statistics and expert opinions on this area are summarized. Introduce the significance of the study in the context of the modern IT-driven world. Define digital risk and highlight the importance of understanding its implications on users' well being. Briefly mention the experts and sources contributing to the definition of digital risk.